Sodium alginate-coconut oil edible coating delayed postharvest senescence and enhanced antioxidant capacity of lemon (Citrus latifolia) fruit - NGUYEN TRUNG TRUC; DUONG THI CAM NHUNG (Smujo International, 2026)
Abstract. Truc NT, Nhung DTC. 2026. Sodium alginate-coconut oil edible coating delayed postharvest senescence and enhanced antioxidant capacity of lemon (Citrus latifolia) fruit. Asian J Agric 10 (1): g100156. https://doi.org/10.13057/asianjagric/g100156. Postharvest quality deterioration of lemon fruit is closely associated with physiological metabolism and oxidative stress during storage. This study investigated the efficacy of Sodium Alginate (SA) and Coconut Oil (CO) coatings, applied individually or in combination, in regulating physiological metabolism, oxidative stress, and antioxidant defense responses of lemon fruit during ambient storage. Fruits were assigned to four treatments (Control, SA, CO, and SA-CO) using a completely randomized design with three replicates per treatment. Coated and uncoated fruits were stored at 25℃ for 18 days, and key physiological (moisture loss, color), biochemical (vitamin C, total phenolics), reactive oxygen species (ROS), and antioxidant enzyme indicators were periodically evaluated. Relative to the control, the combined SA-CO coating markedly delayed deterioration. By day 18, SA-CO treated fruit showed weight loss of about 14%, which was roughly 2.5 percentage points lower than the control. Chlorophyll degradation was reduced, with SA-CO fruit retaining around 185 mg kg-1 chlorophyll, approximately 40 mg kg-1 higher than the control. Antioxidant compounds were better preserved, with vitamin C maintained at nearly 0.29 g kg-1 and total phenolics reaching about 0.15 g GAE kg-1, both slightly higher than the control. The coating also improved antioxidant enzyme regulation. At the end of storage, SOD activity in SA-CO fruit was close to 29 U mg-1 protein, substantially lower than the control, whereas APX and CAT activities increased by about 12 U mg-1 and 25 U mg-1 protein, respectively. Correspondingly, reactive oxygen species decreased, with superoxide radicals recorded at around 1.5 mmol NO₂ kg-1 s-1 and hydrogen peroxide at about 0.8 µmol H₂O₂ kg-1, both noticeably lower than the control. Overall, the combined SA-CO coating most effectively mitigated physiological degradation, improved antioxidant defense responses, and reduced oxidative stress, thereby supporting better retention of postharvest quality in lemon fruit stored under ambient conditions.